Prevalence of risk factors for coronary artery disease in an urban Indian population. Issue 12 (8th December 2014) - Sekhri, T; Kanwar, R S; Wilfred, R; Chugh, P; Chhillar, M; Aggarwal, R; Sharma, Y K; Sethi, J; Sundriyal, J; Bhadra, K; Singh, S; Rautela, N; et al.
Abstract : Objective: The objective of this study was to assess the prevalence of risk factors for coronary artery disease (CAD) in government employees across India. Methods: The study population consisted of government employees in different parts of India (n=10 642 men and n=1966 women; age 20–60 years) and comprised various ethnic groups living in different environmental conditions. Recruitment was carried out in 20 cities across 14 states, and in one union territory. All selected individuals were subjected to a detailed questionnaire, medical examinations and anthropometric measurements. Blood samples were collected for blood glucose and serum lipid profile estimation, and resting ECG was recorded. Results were analysed using appropriate statistical tools. Results: The study revealed that 4.6% of the study population had a family history of premature CAD. The overall prevalence of diabetes was 16% (5.6% diagnosed during the study and the remaining 10.4% already on medication). Hypertension was present in 21% of subjects. The prevalence of dyslipidemia was significantly high, with 45.6% of study subjects having a high total cholesterol/high density lipoprotein ratio. Overall, 78.6% subjects had two or more risk factors for CAD. Conclusions: The present study demonstrates a high prevalence of CAD risk factors in the Indian urban population. Therefore, there is an immediate need to initiate measures to raise awareness of these risk factors so that individuals at high risk for future CAD can be managed.